Immediate Effect of Auriculotherapy on Exam Anxiety among Naturopathy Medical Students: A Protocol for Randomized Controlled Trial - M R, Monicaasun; Narasimman, Prabu; S, NaveenKumar (Indian Journal of Integrative Medicine, 2025)
Background: Anxiety characterized by tension, worries, resulting unfavorable reactions in the physical body. Educational institutions use examinations to evaluate students' learning and comprehension, this may hamper their scholastic performance because of anxiety, which leads to psychosomatic disturbance before, during, and sometimes after tests resulting in exam anxiety. Medical students reported higher rates of anxiety and depression. Extreme anxiety can hinder their ability to manage the stress response during examinations. Anxiety can be effectively managed through complementary and alternative medicines. Auriculotherapy is a less invasive method effectively reducing the anxiety through stimulation of vagus and trigeminal nerves of the ear. Objectives: Primary objective is to assess the immediate effect of auriculotherapy in reducing anxiety levels, heart rate and blood pressure among medical students. Materials and method: This study adapts randomized controlled design. 60 subjects will be recruited by using convenient sampling technique from Naturopathy medical college, Tamil Nadu and randomized into study and control group. Study group will receive auriculotherapy on ear Shenmen and Point Zero for 3 hours whereas control group will not receive any intervention. The assessment will be done 30 mins before the exam and after the completion of the exam (3 hours). Results: The outcome variables are Hamilton Anxiety Rating Scale (HMA-A), Blood pressure (BP) and Heart rate (HR). We have framed the strong hypothesis based on which we expecting positive results on HMA-A scale, HR, and BP. Conclusion: The study will confirm the effect of auriculotherapy on exam anxiety among university exam appearing naturopathy students.